2005
DOI: 10.1161/01.res.0000194329.41863.89
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ /Calmodulin–Dependent Protein Kinase Modulates Cardiac Ryanodine Receptor Phosphorylation and Sarcoplasmic Reticulum Ca 2+ Leak in Heart Failure

Abstract: Abstract-Abnormal release of Ca from sarcoplasmic reticulum (SR) via the cardiac ryanodine receptor (RyR2) may contribute to contractile dysfunction and arrhythmogenesis in heart failure (HF). We previously demonstrated decreased Ca transient amplitude and SR Ca load associated with increased Na/Ca exchanger expression and enhanced diastolic SR Ca leak in an arrhythmogenic rabbit model of nonischemic HF. Here we assessed expression and phosphorylation status of key Ca handling proteins and measured SR Ca leak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

53
630
5
16

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 637 publications
(712 citation statements)
references
References 48 publications
53
630
5
16
Order By: Relevance
“…Whereas PKA phosphorylation of RyR2 is often elevated, reduced phosphorylation levels of PLN (27), cardiac myosin-binding protein C, and troponin I have been reported in failing hearts (28). In the case of dystrophic hearts, Williams et al (5) reported a reduction in PKA phosphorylation of S16 on PLN in mdx mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas PKA phosphorylation of RyR2 is often elevated, reduced phosphorylation levels of PLN (27), cardiac myosin-binding protein C, and troponin I have been reported in failing hearts (28). In the case of dystrophic hearts, Williams et al (5) reported a reduction in PKA phosphorylation of S16 on PLN in mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is emerging evidence that phosphorylation of RyR2 by Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) also plays an role in the regulation of SR Ca 2+ homeostasis and cardiac function in heart failure (27). Because cytosolic Ca 2+ levels are elevated in dystrophic hearts, it is possible that CaMKII is activated and contributes to SR Ca 2+ leak.…”
Section: Discussionmentioning
confidence: 99%
“…However, other groups have not found PKA-dependent hyperphosphorylation in failing hearts (Xiao et al 2005). In addition, other laboratories suggest that CamKII-dependent phosphorylation of RyR2 is involved in enhanced SR Ca 2þ leak and reduced SR Ca 2þ load in heart failure and may contribute to arrhythmias and contractile dysfunction (Ai et al 2005;Chelu et al 2009;Curran et al 2010;Neef et al 2010). Phosphorylation of other targets of these kinases (troponin I, sarcolemmal Ca 2þ channels, and phospholamban) could also alter the Ca 2þ handling in cardiac and skeletal muscle.…”
Section: Pka and Camkii Phosphorylationmentioning
confidence: 99%
“…In animal models of heart failure, changes in phosphoinositide metabolism occur, including alterations in the abundance, expression and/or activity of PIP 2 , PI-4 kinase, PIP-5 kinase, PLC isoforms and inositol phosphates [200,201]. Expression of IP 3 Rs is increased in both human and animal heart failure, whereas RyR levels are reduced, indicating a shift toward more IP 3 R-mediated Ca 2+ release in the failing heart [19,202]. These data indicate that, in heart failure, there are complex changes in the transmitter and receptor systems coupling to IP 3 formation as well as in the regulation of IP 3 Rs suggesting that IP 3 -induced Ca 2+ release is involved in the development and/or progression of the disease.…”
mentioning
confidence: 99%